2020
DOI: 10.1101/2020.01.08.898197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent Met and voltage-gated Ca2+channel signaling on Ras-Erk MAPK drives migratory activation of dendritic cells parasitized byToxoplasma gondii

Abstract: 24Ras-Erk MAPK signaling controls many of the principal pathways involved in 25 metazoan cell motility, drives metastasis of multiple cancer types and is targeted in 26chemotherapy. Yet, its putative roles in immune cell functions or in infections have 27 remained elusive. Here, using primary dendritic cells (DCs) in an infection model with 28 the protozoan Toxoplasma gondii, we show that two pathways activated by infection 29 converge on Ras-Erk MAPK signaling to promote migration of parasitized DCs. We 30 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Ras activation ultimately leads to Erk1/2 phosphorylation via Raf-Mek. Further, Ras-Erk signalling was activated downstream of the receptor tyrosine kinase (RTK) MET, situating Ras as a central signalling node and point of convergence for VGCC and MET signalling (Olafsson et al, 2020). These data are in line with paradigms in neuronal cells, where VGCC-dependent CaM activity regulates cytoskeleton organisation and cell migration via Ras-Erk signalling (Rosen et al, 1994).…”
Section: Major Cell Signalling Axes Of the Hypermigratory Phenotypementioning
confidence: 67%
See 4 more Smart Citations
“…Ras activation ultimately leads to Erk1/2 phosphorylation via Raf-Mek. Further, Ras-Erk signalling was activated downstream of the receptor tyrosine kinase (RTK) MET, situating Ras as a central signalling node and point of convergence for VGCC and MET signalling (Olafsson et al, 2020). These data are in line with paradigms in neuronal cells, where VGCC-dependent CaM activity regulates cytoskeleton organisation and cell migration via Ras-Erk signalling (Rosen et al, 1994).…”
Section: Major Cell Signalling Axes Of the Hypermigratory Phenotypementioning
confidence: 67%
“…As laid out above, autocrine GABAergic signalling is activated in parasitised DCs (Fuks et al, 2012), which in turn triggers VGCC-mediated Ca 2+ influx (Kanatani et al, 2017). More recent data revealed that Ca 2+ influx via the VGCC subtype Ca V 1.3 mediates activation of the small GTPase Ras via calmodulin (CaM) and CaM kinase II (CaMkII) signalling (Olafsson et al, 2020) (Figure 2). Ras activation ultimately leads to Erk1/2 phosphorylation via Raf-Mek.…”
Section: Major Cell Signalling Axes Of the Hypermigratory Phenotypementioning
confidence: 91%
See 3 more Smart Citations